Advances in metabolic engineering of cyanobacteria for production of biofuels. (15th August 2022) - Mund, Nitesh Kumar; Liu, Yisong; Chen, Shaolin
Highlights: Photosynthetic microorganisms can convert CO2 and water into biofuels. Cyanobacteria reflect superior photosynthesis and biomass production capabilities. Cyanobacteria have established genetic backgrounds for genetic manipulations. Metabolic engineering approaches being used in cyanobacteria to generate biofuels. Abstract: Current trends in fossil fuel use, having a direct impact on the global carbon cycle, could potentially be mitigated by adopting the use of biofuels with sustainable features. While bioethanol is currently being used as a major biofuel, especially for transportation worldwide, it is hygroscopic and contains less energy. Therefore, the prospect of biofuels has now shifted to higher alcohols, alkanes, and other molecules that have similar properties to existing gasoline and diesel fuels. Microalgae and cyanobacteria are aquatic photosynthetic microorganisms that can convert CO2 and water into carbon-rich lipids, a substrate for biodiesel production, more efficiently than the agricultural oleaginous crops, making them a superior option to traditional oil-seed crops. Cyanobacteria are gram-negative photosynthetic bacteria that have instrumental roles in global biological carbon sequestration, oxygen evolution, and nitrogen fixation. Furthermore, cyanobacteria have established genetic backgrounds, flexibility in genetic manipulation, and tolerance to the introduction of foreign genes. Metabolic engineering strategies in these photosynthetic hosts have resulted in the conception of cell factories capable of one-step synthesis of biofuel molecules from CO2, light, and water. Two freshwater cyanobacteria species, Synechocystis sp. PCC 6803 ( Synechocystis 6803) and Synechococcus elongatus sp. PCC 7492 ( Synechococcus 7492), and marine Synechococcus sp. PCC 7002 ( Synechococcus 7002) are among the highly studied cyanobacteria for the production of biofuels. Here, we reviewed the recent progress in metabolic engineering and synthetic biology approaches in cyanobacteria for the synthesis of various biofuel molecules, ranging from alcohols to biodiesels and terpenes or terpenoids.